Pemanfaatan Instagram Sebagai Media Penyebaran Informasi dan Promosi di Coffee Shop House of Musi - Stefi Ananta Rivelia; Nurizzati (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The development of social media has encouraged businesses to utilize Instagram as a marketing communication tool, but its effectiveness in disseminating information and building relationships with consumers still needs to be studied. This study aims to describe the use of Instagram as a medium for disseminating information and promotion at Coffee Shop House of Musi. The study used a qualitative approach with descriptive methods. Five research informants were selected using a purposive sampling technique, consisting of Instagram account managers and Coffee Shop House of Musi consumers. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The analysis refers to the Uses and Gratifications theory. The results of the study indicate that Instagram is optimally utilized through structured content planning, delivering information about menus, promotions, and coffee shop activities, and utilizing interactive features that strengthen communication with consumers. Attractive visual content and consistent information increase trust and encourage consumer decisions to visit. This study concludes that Instagram plays a role as a promotional medium as well as an effective marketing communication tool. These findings provide practical implications for coffee shop managers in optimizing social media-based digital marketing strategies.